The Influence Of Compensation And Work Discipline On The Performance Of PT. Employees. Radio Swara Mersidiona Tangerang City - Nurhaedi, Aprilya; Octaviani, Irma Sari (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2025)
This study aims to analyze the effect of compensation and work discipline on employee performance at PT Radio Swara Mersidiona Kota Tangerang, both partially and simultaneously. Using a quantitative method with a saturated sample of 55 employees, data was obtained from respondents' answers. The results show that compensation and work discipline simultaneously have a significant effect on employee performance (Fcal 50.505 > Ftable 3.175, sig. 0.000 < 0.05). Partially, compensation (coefficient 0.617) and work discipline (coefficient 0.392) have a positive and significant impact. The coefficient of determination (R²) of 53.4% indicates that the remaining 46.6% is influenced by other factors.